ANALISIS PENGARUH UKURAN PERUSAHAAN DAN GOOD CORPORATE GOVERNANCE TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2010-2013 - Siti Kholifatin Alfisyah; Azwir Nasir; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is conducted at manufacturing business which enlist in Effect Exchange Indonesia (BEI) with period of year 2010-2013. Population in this research is manufacturing businesss which enlist in Effect Exchange Indonesia (BEI) with period of year 2010-2013 amounting to 129 company contained in IDX 2010-2013. Amount of sampel in this research counted 37 company, method intake of sampel conducted by using sampling purposive. While to analyse data, writer use doubled linear regression o] version 17.00. Result of coefficient test of determinasi known that value of R Square in this research equal to 0,670. This matter indicate that by together company size measure variable, concentration of[is ownership of manajerial, board of comisioner composition, audit committee composition give influence which is signifikan equal to 67,0 % to make-up of management earning at manufacturing business which enlist in BEI 2010 - 2013, while the rest equal to 33,0 % influenced by other variable which do not in research in this research. As for such other varabel is independent commissary, quality of board of comisioner, quality of audit committee, execution of RUPS and institutional ownership.Keywords: Earning Management, Size measure Company, Concentration of is ownership of manajerial, board of comisioner composition, and audit committee composition.